2021
DOI: 10.2147/ppa.s298537
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care in Type 2 Diabetes Patients with Urgency Lower Limb Amputation: The Influence of Sex, Marital Status and Previous Amputations

Abstract: Aim: Lower limb amputation (LLA) is a severe consequence of type 2 diabetes mellitus (T2DM), and can affect up to 1% of T2DM patients, leading to an increased risk of premature mortality. Among the factors to predict LLA, it has been highlighted sex, marital status, and previous amputation. However, there is a lack of information about the association between these predictive factors, self-care, and urgency LLA in T2DM patients. Purpose: To verify the behavior of self-care and to relate it with the predictive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
5
2
Order By: Relevance
“…Unlike a previous study (Domingos et al, 2021 ), our study showed that marital status is one of the important predictors of foot self‐care behaviour among T2D adults without comorbid HF. The current study suggests that adults with T2D are married were less likely to perform the recommended foot self‐care behaviours.…”
Section: Discussioncontrasting
confidence: 97%
“…Unlike a previous study (Domingos et al, 2021 ), our study showed that marital status is one of the important predictors of foot self‐care behaviour among T2D adults without comorbid HF. The current study suggests that adults with T2D are married were less likely to perform the recommended foot self‐care behaviours.…”
Section: Discussioncontrasting
confidence: 97%
“…The results of this study are inconsistent with previous research, which stated that gender has a significant effect on foot care behavior (Domingos et al, 2021;Pourkazemi et al, 2020;Sharoni et al, 2017;Usta et al, 2019). Females look better in foot care, painstaking, and more capable of doing foot care than males (Usta et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…Individual sociodemographic characteristics are essential in self-care behavior as a diabetic foot ulcer prevention effort. Several previous studies have shown that sociodemographic factors influence foot care behavior, including age (Miikkola et al, 2019;Sari et al, 2020), gender (Domingos et al, 2021;Pourkazemi et al, 2020;Sharoni et al, 2017;Usta et al, 2019), marital status (Domingos et al, 2021;Pourkazemi et al, 2020), an education level (Ahmed et al, 2019;D'Souza et al, 2016;Pourkazemi et al, 2020;Sari et al, 2020;Syed et al, 2019), income level (D'Souza et al, 2016;Khaliq et al, 2019;Syed et al, 2019), family system/type or support (D'Souza et al, 2016;Sari et al, 2020), and ethnicity (Nwasuruba et al, 2007;Tan et al, 2020). Older people with T2DM often experience difficulty carrying out self-care, including foot selfcare behavior (Miikkola et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each thrombectomy was performed 3 times, the flow was present after each thrombectomy, but it weakened again. Subsequently, a lower-extremity amputation procedure (digit I pedis dextra) was performed [10] . The condition of the patient's legs before and after the amputation can be seen in Fig.…”
Section: Case Presentationmentioning
confidence: 99%